2011
DOI: 10.18388/abp.2011_2286
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products and inflammatory markers in liver cirrhosis: a comparison between alcohol-related and HCV-related cirrhosis.

Abstract: Advanced oxidation protein products (AOPPs) are protein markers of oxidative stress with pro-inflammatory properties that accumulated in liver cirrhosis. In the present study, we investigated the association between chronic inflammatory response triggered by AOPPs and the severity of liver disease as assessed by the Child-Pugh score. Plasma concentrations of AOPPs and inflammatory markers such as C-reactive protein, tumor necrosis factor-α, and interleukin-6 were measured in 41 patients with HCV-related cirrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…In contrast, other studies have shown elevated CRP levels in CHC infection . In a study of patients with angiographically documented CAD, CRP, and fibrinogen levels were significantly elevated in HCV‐infected patients compared to controls and HCV seropositivity was associated with increased severity of CAD .…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…In contrast, other studies have shown elevated CRP levels in CHC infection . In a study of patients with angiographically documented CAD, CRP, and fibrinogen levels were significantly elevated in HCV‐infected patients compared to controls and HCV seropositivity was associated with increased severity of CAD .…”
Section: Resultsmentioning
confidence: 69%
“…21 TNF-dependent processes are up regulated and activated in CHC, and TNF-α mRNA is ubiquitously expressed in hepatocytes, Kupffer cells, and infiltrating mononuclear cells at higher levels in CHC patients than in healthy controls. 22,23 31 Falasca et al 32 Helaly et al 33 Khan et al 34 Migita et al 36 Zekri et al 37 Malaguarnera et al 38 Costantini et al 39 Capone et al 40 Oyanagi et al 41 Lapinski et al 42 Lecube et al 43 Sandler et al 44a Grungreiff et al 46a Cotler et al 48a Hung et al 49 Antonelli et al 50 Shive et al 52 Cua et al 53 Grungreiff et al 54 Lee et al 84 Mishra et al 87 Sousa et al 91 Tsui et al 35 Zuwała-Jagiełło et al 57 Mourtzikou et al 58 Han et al 85 Müller et al 92…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid peroxidation and advanced oxidation protein products as well as 8-hydroxydeoxyguanosine (8-OHdG) are ROS-modified biological molecules, and were found at significantly higher levels in PBMCs in HCV patients compared to healthy controls ([19,28,29,32,33,34,39,40] and others). Significant increase of 8-OHdG was detected in situ in liver samples from CHC patients [41].…”
Section: Oxidative Stress In Patients With Chronic Hepatitis Cmentioning
confidence: 99%
“…Although structure of several AGEs has been reported, it has been demonstrated that Nε‐(carboxymethyl) lysine (CML) is the major antigenic AGE structure . Serum concentration of CML is also increased in diabetic patients with complications like nephropathy , retinopathy and atherosclerosis . CML is also recognized by RAGE and the interaction of CML–RAGE activates signaling pathways like NF‐B .…”
Section: Immunochemical Techniques Used For Detection and Measurementmentioning
confidence: 99%